FORMS OF PLACEMENT OF CHILDREN DEPRIVED OF PARENTAL CARE: NATIONAL AND FOREIGN LEGISLATION (TAMADDUN NURI JURNALI, 2024)
This article provides a comparative analysis of the issues of housing children deprived of parental care and ensuring their social protection. First of all, the experience of national legislation and foreign countries is studied. Then in this area, the legislation in force in Uzbekistan is studied. The summary section provides specific proposals and recommendations for improving national legislation.